Inquiry Project Laboratory: The Collaborative Problem Solving and Critical Thinking on Laboratory - Hendri Saputra; Juli Firmansyah; Ahmad Ihsan (Jurnal Penelitian Pendidikan IPA, 2023)
Collaborative problem-solving is one of the important soft skills in project-based laboratory activities to equip students with critical thinking skills. A study that systematically reviews literature relevant to the successful implementation of the Inquiry Project Laboratory (IPro-Lab) which is carried out in 5 main stages. A systematic review of relevant qualitative research findings using an integrative approach to gain a deeper understanding (meta-synthesis) through summarization techniques (meta-aggregation). The review stage begins with extracting relevant studies, identifying important findings, categorizing findings, and developing a conceptual framework. The studies and reviews are focused on the success of the IPro-Lab practicum in equipping critical thinking, creative, collaboration and communication skills. In addition, it was also found that the successful track record of the IPro-Lab practicum has been tested and valid to support the formation of scientific thinking, solving complex problems and the needs of the 21st century. IPro-Lab also provides opportunities for the self-development of teachers so that they are more innovative, creative and structured